Concrete Operators, Spectral Theory, Operators in Harmonic Analysis and Approximation 22nd International Workshop in Operator Theory and its Applications, Sevilla, July 2011 - Cepedello Boiso, Manuel; Hedenmalm, Håkan; Kaashoek, Marinus A.; Montes Rodríguez, Alfonso; Treil, Sergei (Operator Theory: Advances and Applications, 2014)
This book contains a collection of research articles and surveys on recent developments on operator theory as well as its applications covered in the IWOTA 2011 conference held at Sevilla University in the summer of 2011. The topics include spectral theory, differential operators, integral operators, composition operators, Toeplitz operators, and more. The book also presents a large number of techniques in operator theory.